2011
DOI: 10.2214/ajr.10.6058
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Effect of Vendor Variability in CT Perfusion Results: A Method Comparison Study

Abstract: Different vendor software applications do not generate quantitative perfusion results equivalently. Intervendor difference is, by far, the largest cause of variability in perfusion results relative to interoperator and intraoperator difference. Caution should be exercised when interpreting quantitative CT perfusion results because these values may vary considerably depending on the postprocessing software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 11 publications
0
45
1
Order By: Relevance
“…27 CT perfusion needs algorithms for postprocessing images that are vendor-specific, not standardized, and therefore variable across centers. [28][29][30][31] Trained personnel are sometimes needed to process these images. In addition, image quality is affected to some extent by patient motion.…”
Section: Discussionmentioning
confidence: 99%
“…27 CT perfusion needs algorithms for postprocessing images that are vendor-specific, not standardized, and therefore variable across centers. [28][29][30][31] Trained personnel are sometimes needed to process these images. In addition, image quality is affected to some extent by patient motion.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recently, it was shown that intravendor differences are the primary cause of the variability in CTP analysis. 13 In this study, we have assessed the reproducibility of the CTP analysis summary maps between both methods, rather than the accuracy of either method. We, therefore, abstain from any judgment on which package is more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…12 A more recent study showed that intervendor differences constituted the primary cause of the variability in CTP analysis results in a population of 11 patients. 13 In this study, we assessed quantitative differences in CTP summary maps between 2 software packages analyzing identical CTP source images. These 2 software packages represent the 2 mainstream algorithms: delay-sensitive and delay-insensitive.…”
mentioning
confidence: 99%
“…Actually, software differences constitute the primary cause of variability in perfusion results relative to interoperator and intraoperator differences. [20][21][22] The strength of our study is that we used equipment from the same manufacturer and used the same post-processing procedure for all subjects. Furthermore, both experienced neuroradiologists independently drew two standardized elliptical mirrored ROIs (an area of approximately 5 cm each) on the section level of the reference CT image (Figure 1a) over the cortical grey matter of the middle cerebral artery territory.…”
Section: Discussionmentioning
confidence: 99%